PENGARUH METODE BERMAIN PUZZLE TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK PRA SEKOLAH DI TAMAN KANAK-KANAK KECAMATAN SIANTAR KOTA TAHUN 2020 - Tedty Rohaya Tinambunan (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Abstract Introduction : Preschool children are children aged between there to six years which in this phase is known as the golden age. At this time children often experience delays in fine motor skills due to writing and drawing, this causes the act of using small muscles not according to age. One of the games that can improve the act of using small musclesis by playing puzzles.Puzzle is on of medium to stimulate the act of using small muscles. The research aimed to find the effect of “ puzzle playing method “ toward the act of using small muscles of preschool children. The research menthod used pre experiment one group pretest posttest and involving sampel of 18 respondents which selected by using purposive sampling. The experiment was carried out twice a week for 1 month. Fine motor development before having had not balanced and developed yet and started to develop 50,0 %, after playing puzzles on avarage to 44,4 % developing as expected. Out put results show the results of significance calculations : test saphiro-wilk = <0,05 ( data not normally distributed ). Therefore, the tests that used to make hypotheses cannot use parametric statistical calculations, with uji T-sampel test in pairs ( t dependent ) so it was replaced by a non-parametric tes that is wilcoxon test.